Measuring Tourist Satisfaction with Route Analysis as a Business Advantage - Sutriani, Sutriani; Pristiyono, Pristiyono; Lubis, Junita (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2021)
Although covid-19 is increasingly haunting the world, it has not reduced local investors to develop service businesses and place them as a type of business that is quite developed because it is directly related to consumer satisfaction. loyal customers who have become members of Mirota Swimming Pool. Technical analysis of data using path analysis with SPPS and Amos applications as a tool to determine the significant effect of the proposed hypothesis. The results of the study prove that facilities have a direct effect on tourist satisfaction, service quality has a significant effect on tourist satisfaction, facilities have a significant effect on business excellence, service quality has a significant effect on business excellence and tourist satisfaction has a significant effect on business excellence. The hope is that local tourism business developers Mirota Ajamu Swimming Pool in coastal areas can expand their business through various promotions and advertisements to improve their image and introduce their business to outsiders. For other research, it is expected to be able to develop the phenomenon by looking for sources of relevant variables that are closely related to satisfaction